2002
DOI: 10.1097/00002030-200208160-00009
|View full text |Cite
|
Sign up to set email alerts
|

Non-typhoidal salmonella bacteraemia among HIV-infected Malawian adults: high mortality and frequent recrudescence

Abstract: NTS bacteraemia has a high mortality (47%) and recurrence (43%) rate in HIV-infected African adults. Recurrence is caused by recrudescence rather than re-infection. As focal infections were rarely found, recrudescence may often be a consequence of intracellular tissue sequestration. There is an urgent need for improved primary treatment and secondary prophylaxis in Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
206
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(211 citation statements)
references
References 34 publications
2
206
0
3
Order By: Relevance
“…An equilibrium is most likely established between host and pathogen whereby opsonizing antibody gives the host the advantage, whereas in the absence of antibody, T helper 1 cytokines (11, 12), or functional oxidative burst mechanism (8, 9), intracellular Salmonellae survive. Only small numbers of bacteria need avoid cell killing in this intracellular niche to establish latent infection that can subsequently reactivate leading to recrudescence of invasive disease, as commonly observed in HIV-infected African adults (14) and subjects with defective T helper 1 immunity (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An equilibrium is most likely established between host and pathogen whereby opsonizing antibody gives the host the advantage, whereas in the absence of antibody, T helper 1 cytokines (11, 12), or functional oxidative burst mechanism (8, 9), intracellular Salmonellae survive. Only small numbers of bacteria need avoid cell killing in this intracellular niche to establish latent infection that can subsequently reactivate leading to recrudescence of invasive disease, as commonly observed in HIV-infected African adults (14) and subjects with defective T helper 1 immunity (11).…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence for the importance of cellular immunity in protecting against Salmonella in man is shown by the high frequency of severe Salmonella infections in individuals with defects in the IL-12/23-IFN-γ axis (11,12), IFN-γ from CD4 + lymphocytes and NK cells being important for activating macrophages to produce an oxidative burst. Both in Africa and worldwide, individuals with HIV/AIDS, especially those with low CD4 + lymphocyte counts (13), are particularly vulnerable to fatal NTS infection (1,(14)(15)(16).…”
mentioning
confidence: 99%
“…Yet, although humans deficient in these host defenses show enhanced susceptibility to nontyphoidal Salmonella infections, they do not appear to be appreciably more susceptible to S. Typhi (de Jong et al 1998;Winkelstein et al 2000;Ottenhoff et al 2002). Similarly, mice lacking CD4 þ T cells are highly susceptible to S. Typhimurium, as are humans with low CD4 þ T-cell counts owing to HIV infection (Fischl et al 1986;Hess et al 1996;Gordon et al 2002), but HIV infection does not confer an increased susceptibility to typhoid fever (Gordon 2008). To render mice susceptible to an S. Typhi challenge, hog gastric mucin must be coadministered to incapacitate host phagocytes, or massive bacterial inocula must be given (Collins and Carter 1978;Hone et al 1991).…”
Section: Humanized Micementioning
confidence: 99%
“…The most frequent serovar in HIV infection is S. Enteritidis. Recently, GORDON et al (2002) has shown high mortality (47%) and frequent recrudescence (43%) with non-typhi Salmonella bacteraemia among HIV-infected Malawian adults.…”
Section: Human Infections Associated Withmentioning
confidence: 99%